Analysis of Immunochemical Parameters in Vertebrogenic Pain Syndrome - Levashova, A.I.; Myagkova, M.A. (Biomedical Chemistry: Research and Methods, 2018)
The immune system can react to pain by synthesis of the natural antibodies to pain-regulating mediators which affec t the nervous system. In this study, the analysis of content antibodies to opioid peptides (β-endorphin and orphanin FQ) and biogenic amines (serotonin and dopamine) in vertebrogenic pain syndrome (PS) was carries out in serum of PS patients. It has been found that this PS is accompanied by an increase in the production of antibodies to the neurotransmitters studied, and the immune response to opioid peptides is more profound than to biogenic amines. The antibodies levels were higher in female patients than in males (especially for orphanin FQ). These data indirectly correlate with the PS intensity and the dynamics of its regression, evaluated using a visual analogue scale (VAS). Thus, the pain intensity measured by VAS in women was higher, in compare with men and the dynamics of decrease was lower. In addition, it was found that during the significant decrease of the pain intensity, there was no significant decrease in antibody levels to antinociceptive mediators. Apparently, this observation indicates the antibodies to antinociceptive mediators can effect the mechanisms of transition from acute to chronic pain and in maintenance of chronic pain.